2004
DOI: 10.1016/j.cub.2004.11.050
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila Wee1 Kinase Regulates Cdk1 and Mitotic Entry during Embryogenesis

Abstract: Cyclin-dependent kinases (Cdks) are the central regulators of the cell division cycle. Inhibitors of Cdks ensure proper coordination of cell cycle events and help regulate cell proliferation in the context of tissues and organs. Wee1 homologs phosphorylate a conserved tyrosine to inhibit the mitotic cyclin-dependent kinase Cdk1. Loss of Wee1 function in fission or budding yeast causes premature entry into mitosis. The importance of metazoan Wee1 homologs for timing mitosis, however, has been demonstrated only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
84
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(92 citation statements)
references
References 22 publications
7
84
0
Order By: Relevance
“…The functional inhibition of Cdk1/cyclin B1 activity by DEDD appears to be specific for mammalian cells, because DEDD (or DEDD homologues) have not been found in databases for lower eukaryotes. This is also consistent with the fact that cell growth before cell division is not significantly affected by the loss of Wee1-related kinases, responsible for phosphorylation of Thr-14/Tyr-15, in higher mammalian cells (4,5,9,10,(14)(15)(16)(17)(18). It is interesting that, in DEDD Ϫ/Ϫ cells, the length was decreased not only in mitosis but also in the G 1 phase (where Cdk1/cyclin B1 is not involved) during cell cycle.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The functional inhibition of Cdk1/cyclin B1 activity by DEDD appears to be specific for mammalian cells, because DEDD (or DEDD homologues) have not been found in databases for lower eukaryotes. This is also consistent with the fact that cell growth before cell division is not significantly affected by the loss of Wee1-related kinases, responsible for phosphorylation of Thr-14/Tyr-15, in higher mammalian cells (4,5,9,10,(14)(15)(16)(17)(18). It is interesting that, in DEDD Ϫ/Ϫ cells, the length was decreased not only in mitosis but also in the G 1 phase (where Cdk1/cyclin B1 is not involved) during cell cycle.…”
Section: Discussionsupporting
confidence: 84%
“…In contrast, an inadequate duration before division, due to aberrant phosphorylation of Tyr-15, causes cells to enter mitosis before sufficient growth, resulting in decreased size of the daughter cells (14-17). Interestingly, the loss of Wee1-related kinases, responsible for phosphorylation of Thr-14/Tyr-15, causes premature cell division in yeast, Xenopus, or Drosophila cells, but not in higher mammalian cells (4,5,9,10,(15)(16)(17)(18). This suggests the presence of alternative mechanism(s), which may also influence cell size, particularly in mammalian cells.…”
mentioning
confidence: 99%
“…Previous studies of Drosophila Wee1 and Myt1 revealed that these conserved Cdk1 inhibitory kinases were required during early embryogenesis and gametogenesis, respectively (Price et al 2000;Stumpff et al 2004;Jin et al 2005). We have now characterized imaginal and adult developmental defects caused by loss of dMyt1 activity (and to a much lesser extent, dWee1), that confirm the importance of Cdk1 inhibitory phosphorylation for coordinating cell-cycle events with critical developmental processes.…”
Section: Discussionsupporting
confidence: 74%
“…In contrast, Wee1 kinases appear to phosphorylate Cdk1 exclusively on the Y15 site (Parker et al 1995). Drosophila dWee1 also functions as a Y15-specific Cdk1 inhibitory kinase, in vitro (Campbell et al 1995) and early embryos (Price et al 2000;Stumpff et al 2004).…”
Section: /Myt1mentioning
confidence: 99%
See 1 more Smart Citation